Analisis Tingkat Kepuasan Pasien terhadap Pelayanan Poli Rawat Jalan di RSUD dr. Abdoer Rahem Situbondo Menggunakan Metode Algoritma C4.5 - Alfira Risma Lutfiyansyah; Lutfi Ali Muharom; Luluk Handayani (Jurnal Penelitian Teknologi Informasi dan Sains, 2024)
The aftermath of the COVID-19 pandemic has had a real impact in all areas of life, especially in the health sector. Therefore, there are consequences of this phenomenon, namely changes in rules and services in the health sector, especially in hospitals. With this change, patients feel different services and rules in the hospital, this has an impact on the hospital, namely the assessment of patient satisfaction with the hospital. The purpose of this study is to measure the accuracy, precision, and recall of the patient satisfaction level grouping. In addition, it also analyzes the shortcomings of hospital services. The method used to build a patient satisfaction classification model is the C4.5 algorithm. C4.5 algorithm is one method that can solve cases that are often used in classification technique problems. The result of the C4.5 algorithm is in the form of a decision tree as in other classification techniques. Based on the results of 3 tests conducted for patient satisfaction at RSUD dr. Abdoer Rahem Situbondo using rapid miner and with the decision tree, the greatest accuracy is 95.38%.